2011
DOI: 10.1111/j.1399-0039.2010.01627.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MICA‐TM, MICB‐C1_2_A and C1_4_1 microsatellite polymorphisms on the susceptibility to chronic periodontitis in Germany

Abstract: The major histocompatibility complex class I chain-related gene A (MICA)-TM exon 5 trinucleotide polymorphism, the MICB-C1_2_A intron 1 dinucleotide polymorphism and the tetranucleotide polymorphism C1_4_1 located in the major histocompatibility complex class I region on chromosome 6 were shown to influence various chronic inflammatory conditions. We investigated the association of these microsatellite polymorphisms with chronic periodontitis, a highly prevalent oral inflammatory disease in 389 periodontitis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A growing body of research now shows that MICB polymorphism is related to certain diseases . However, as HLA‐MICB‐MICA haplotypes have been reported in different people , this disease association may be secondary and due to LD with HLA alleles. Some reported MICA‐MICB haplotypes were confirmed in our study, for example, MICB*005:02 was in strong LD with MICA*010 , and MICB*008 displayed distinct LD patterns with MICA*002:01 in the Li population.…”
Section: Mica Allele Frequencies In Hainan LI Populationmentioning
confidence: 99%
“…A growing body of research now shows that MICB polymorphism is related to certain diseases . However, as HLA‐MICB‐MICA haplotypes have been reported in different people , this disease association may be secondary and due to LD with HLA alleles. Some reported MICA‐MICB haplotypes were confirmed in our study, for example, MICB*005:02 was in strong LD with MICA*010 , and MICB*008 displayed distinct LD patterns with MICA*002:01 in the Li population.…”
Section: Mica Allele Frequencies In Hainan LI Populationmentioning
confidence: 99%
“…Selection of study participants was performed on the basis of a standardized periodontal examination procedure, as described previously (17). The diagnosis of periodontitis was made on the basis of the following clinical and radiographic criteria: (i) a total of at least 15 teeth in situ ; (ii) eight or more teeth with a diagnosis of periodontitis clinically defined as a probing pocket depth of ≥ 5 mm and/or attachment loss of ≥ 2 mm at least at one location and/or a furcation involvement of ≥Class II.…”
Section: Methodsmentioning
confidence: 99%
“…Some MIC molecules are receptors on NK cells, T4 cells, and T8 cells that mediate host antitumor immune response (Kopp et al, 2009). Recently, Folwaczny et al (2011) demonstrated the association between the MIC SNPs and the susceptibility to chronic periodontitis. Some MIC genetic variation was also associated with ulcerative colitis (Li et al, 2010).…”
Section: The G-g-g-t-t-t-t-g-g and C-g-g-t-t-t-t-a-amentioning
confidence: 99%
“…MICA was found to be associated with Addison's disease (Gambelunghe et al, 1999), Behcet disease (Mizuki et al, 1997), etc. Some MICA polymorphisms have been shown to influence various chronic inflammatory conditions (Folwaczny et al, 2011). Some MIC gene polymorphisms and expressions are associated with autoimmune diseases (Li et al, 2010).…”
Section: The G-g-g-t-t-t-t-g-g and C-g-g-t-t-t-t-a-amentioning
confidence: 99%